Functional efficiency of pancreatic cell-engineered construct in an animal experimental model for type I diabetes - N. V. Baranova; A. S. Ponomareva; L. A. Kirsanova; A. O. Nikolskaya; G. N. Bubentsova; Yu. B. Basok; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2024)
The creation of a cell-engineered pancreatic construct (CEPC) from islets of Langerhans and biocompatible matrix carrier (framework/scaffold), which imitates the native microenvironment of pancreatic tissue, is an approach to the treatment of type I diabetes mellitus (T1D).The objective of this work is to conduct a comparative analysis of the functional efficacy of CEPC and isolated rat islets of Langerhans after intraperitoneal administration into rats with experimental T1D.Materials and method. T1D was induced in rats by injecting low-dose (15 mg/ kg) streptozotocin (STZ) for 5 days. CEPC samples were created using viable and functional allogeneic isolated islets of Langerhans and tissue-specific scaffold obtained by decellularization of human pancreatic fragments. The rats received intraperitoneal injection of allogeneic islets of Langerhans (experimental group 1, n = 4) and CEPC (experimental group 2, n = 4). Control group rats received no treatment (n = 4). Blood glucose levels in the rats were measured, and the pancreas and kidneys of the experimental animals were examined histologically. The follow-up period for all animals continued for 10 weeks. Results. In experimental group 1, on day 7 after injection of Langerhans islets, glycemia decreased significantly from 28.2 ± 4.2 mmol/L to 13.4 ± 2.6 mmol/L. This fall persisted for 7 weeks, following which blood sugar increased to nearly their initial levels (prior to islets administration). In experimental group 2, on day 7 after CEPC administration, there was a more noticeable drop in blood sugar levels from 25.8 ± 5.1 mmol/L to 6.3 ± 2.7 mmol/L compared to experimental group 1. By the 10th week of the experiment, the average glucose level was two times lower than it was at the beginning. Blood glucose levels dropped more sharply in the CEPC group than in the islet group (by 75.6% and 52.5%, respectively).Conclusion. In T1D rats, CEPC has a more potent antidiabetic effect than islets of Langerhans. Thus, it has been shown that a tissue-specific scaffold may be used to create bioartificial pancreas in order to increase the functional efficiency of islets.